Inventarisasi Tumbuhan Obat Di Kawasan Diklatsar Tlogodringo Tawamangu Jawa Tengah Sebagai Bahan Sosialisasi Bagi Masyarakat - Santoso, Eka Andy; Suryani, M.Sc., Dra. Titik Suryani, M.Sc (2016)
Tlogodringo was region which had a summit elevation of 2.054 m. asl to 1.700 m. asl initial altitude with high diversity of medicinal plants. Medicinal plants were all planted that all parts of the body can be used as a drug that was able to provided a healing effect. The ains of study was to determined the types of herbs that are located of DIKLATSAR Tlogodringo. The methods were random sampling and exploration to record and identified medicinal plants at any altitude. The results of the research discovere 15 species of medicinal plants with the dominant families are Poaceae, namely plants is blady grass (Imperata cylindrica) an altitude 1.700 m. asl and discovere 10 species of medicinal plants with the dominant families are Asteraceae, namely plants is teklan (Eupatorium riparium) an altitude 1.900 m. asl in DIKLATSAR hill track of Tlogodringo. The most medicinal plants are inventoryat an altitude of 1.700 m. asl.Based on study concluded that higher the altitude less diversity of medicinal plants.